Kritik Nalar Arab: Eksposisi Epistemologi Bayani, ‘Irfani dan Burhani Muhammad Abed Al-Jabiri - AHMAD HASAN RIDWAN (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2016)
This article anaylizes the philosophical and episthemological exposition of the contemporary Arab thinker, Muhammad Abed Al-Jabiri. As a leading Maroccan Muslim thinker, Abed al-Jabiri in renowned for his idea of combating‘irrationalism’ and that of promoting rasionalism in formulating Islamic thought. He comes to believe that Islamic teachings should be seen as a set of ideas com- patible with rationality and scientific notions. In his analyisis, Abed al-Jabiri pro- poses three streams of Islamic epistemological models: bayani, burhani and ‘irfani. By exploring these three epistemological concepts, the author goes further by exploring the authority of text in Muslim society and how to contextualize and read religious texts in modern time.